Participant lived experiences of high-intensity interval training in UK cardiac rehabilitation (HIIT or MISS UK): A qualitative study - Charlotte Williams; Richard Neil; Richard Powell; Brian Begg; Stefan Birkett; Simon Nichols; Stuart Ennis; Prithwish Banerjee; Lee Ingle; Rob Shave; Gordon McGregor (PLoS ONE, 2026)
Background Exercise programmes are an important component of comprehensive cardiac rehabilitation (CR). High Intensity Interval Training (HIIT) has been proposed as an alternative to conventional moderate intensity steady state (MISS) exercise. In the ‘HIIT or MISS UK’ trial, low-volume HIIT was safe, and clinically and cost effective. However, there is a lack of insight into the lived experiences of those who engage in non-conventional approaches to CR exercise training. The aim of this research was to explore the benefits and challenges associated with HIIT and MISS in CR. Materials and methods A qualitative descriptive methodology was adopted to document participant lived experiences. Participants were purposefully recruited from two ‘HIIT or MISS UK’ trial CR centres. After consent, participants took part in semi-structured interviews conducted via Voice over Internet Protocol (VoIP) technologies (e.g., Microsoft Teams (MT), Skype or Zoom). A critical realist approach to inductive thematic analysis was used to analyse the data. Findings 19 people took part (8 MISS and 11 HIIT; male 18 [95%]; age 59.6 years [SD 10.4]). Analysis revealed a range of perceived psychosocial (e.g., enjoyment, confidence, purpose) and physiological (e.g., weight loss, increased fitness) benefits that were present across both groups (i.e., HIIT and MISS). Participants in both groups identified challenges, for example, a need for exercise to continue beyond what was offered in the trial. There were notable differences across the groups, namely HIIT participants enjoyed feeling challenged, yet grappled with feelings of monotony, whilst MISS participants experienced increased social interaction. Conclusion HIIT in CR offered a range of perceived psychosocial and physiological benefits. Integrating more opportunities for social interaction into the HIIT program could enhance participant experience. Practitioners could investigate the feasibility of support for patients after CR has finished.